Literasi Keuangan dan Media Sosial sebagai Determinan Minat Investasi Logam Mulia: Peran Self-Control sebagai Mediator - Dessy Dwiyanti (Graha Mitra Edukasi, 2026)
This study aims to analyze the influence of financial literacy and social media on precious metal investment interest, with self-control serving as a mediating variable among students at Gunadarma University. The study employed a quantitative approach using an explanatory research design to examine the causal relationships among the variables. Primary data were collected through an online questionnaire distributed via Google Forms to 92 students selected using a purposive sampling technique. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The model evaluation consisted of outer model assessment through convergent validity, discriminant validity, and construct reliability tests, as well as inner model assessment through the coefficient of determination (R²), effect size (f²), and path significance testing using the bootstrapping procedure. The findings indicate that financial literacy and social media have a positive and significant effect on precious metal investment interest. Furthermore, financial literacy has a positive and significant effect on self-control. In contrast, social media has no significant effect on self-control, and self-control also has no significant effect on precious metal investment interest. The indirect effect analysis further reveals that self-control does not mediate the relationship between financial literacy and social media and precious metal investment interest. This study contributes to the development of Behavioral Finance Theory by demonstrating that cognitive factors, namely financial literacy and access to investment information through social media, play a more prominent role in fostering interest in precious metal investment than psychological factors such as self-control. The findings also provide practical implications for higher education institutions, financial institutions, and investment service providers in designing financial literacy education programs and optimizing social media as an effective channel to enhance investment interest among Generation Z.